Areas of endemism in the Espinhaço Range in Minas Gerais, Brazil - Echternacht, Livia; Trovó, Marcelo; Oliveira, Caetano T.; Pirani, José Rubens (Flora. Morphologie, Geobotanik, Oekophysiologie, 2011)
The Espinhaço Range, a mountain chain located in the Brazilian states of Minas Gerais and Bahia, contains one of the richest floras in Brazil, with a high frequency of endemic species. Since 2005 it is designated as UNESCO biosphere reserve and is situated at the joint border of two global hotspots for biodiversity conservation. Endemic species with congruent occurrence patterns were identified in order to establish areas of higher endemism within the Espinhaço Range. Taxonomic reviews were analyzed in order to identify endemic taxa and a dataset was elaborated containing 1765 records from 178 endemic species of vascular plants, representing 17 families and including the geographic coordinates for each record. Two maps were produced showing species richness and collection effort in 15′ quadrats. The congruent occurrences were identified and a third map was provided, delimiting 10 candidate areas of endemism for a “parsimony analysis of endemicity” (PAE). One most parsimonious cladogram is then retrieved, evidencing three major clades corresponding to the northern, central and southern portions of the Espinhaço, in addition to four subclades included into the central clade. We finally identified six major areas of endemism. Furthermore, there is a strong correlation between species richness and collector effort, revealing which areas are in need of further field inventories.